What Are the Firm Value Implications of SEC-Challenged Shareholder Proposals? - Couvert, Maxime (Management Science, 2025)
The Securities and Exchange Commission (SEC) permits managers to request the exclusion of shareholder-initiated proposals. I construct a novel data set of excluded and withdrawn proposals from the SEC’s responses to managers’ requests. An examination of announcement returns to withdrawal and exclusion decisions demonstrates that SEC-challenged proposals are value destroying. I find that special interest investors pursuing self-serving agendas and retail investors advocating for one-size-fits-all reforms explain the value-destroying nature of SEC-challenged proposals. On average, the SEC challenge benefits firm value by filtering out these harmful proposals. However, a regression discontinuity design reveals that proposals the SEC refuses to exclude may receive majority shareholder support and destroy firm value. This paper was accepted by Suraj Srinivasan, accounting. Funding: I thank the Swiss Finance Institute for its generous financial support. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.01344 .